A Perancangan Ilustrasi Board Game Mudik Dalam Keselamatan Berkendara - Edwin Sanggra; Jasson Prestiliano; T Arie Setiawan (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2019)
One thing that should come before everything else in driving is safety. If someone ignores traffic light while driving, it must be dangerous for motorists. The way to overcome this ignorance is giving information about the safety while riding motorcycle to young-adult since they like to violate the traffic law. The information about safety riding from the police seems not be delivered well to the audience, but now this information can be applied on board game. Board game needs an illustration as the main element. The illustration used must be compatible with the player to make it interesting. The illustration of board game is the main key for the game so that the message can be delivered well. The illustration of board game ‘Mudik Yuk’ is designed based on the data from police regarding to violation of traffic law, especially in Indonesia. The board game ‘Mudik Yuk’ is expected to reduce the number of traffic rule’s violation. Keywords: safety riding, Visual and Communication Design, board game, illustration